EARLY FLUID THERAPY IN NEUROCRITICAL CARE: DIAGNOSIS-SPECIFIC MORTALITY PATTERNS FROM AN OPEN DATASET ANALYSIS - Firdaus, Indy Zahrotul; Sitepu, Imanuel Suranta Pemerana; Putri, Syarellia Syafira; Ferdian, Farrel Rafif; Ernanda, Shelby Amrus; Rakhmatiar, Rodhiyan (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: Neurocritical conditions such as traumatic brain injury, stroke, and brain tumor contribute significantly to mortality. Fluid balance is a key determinant of outcome, as overload can exacerbate brain edema and intracranial hypertension. However, diagnosis-specific evidence remains limited. Objective: To investigate the association between early fluid balance and in-hospital mortality across major neurocritical diagnoses through secondary analysis of a large critical care dataset. Methods: We conducted a secondary analysis using a publicly available dataset from Harvard Dataverse. Adult patients with neurocritical diagnoses were identified, and cumulative fluid balance within the first 72 hours was calculated. Patients were stratified by diagnosis and categorized into positive (>0 mL) or negative fluid balance groups. The primary outcome was in-hospital mortality. Results: A positive early fluid balance was likely correlated with higher mortality across the cohort even without having significant correlation (OR 0.205, 95% CI 0.031–1.301, p=0.093). The effect was strongest for SAH (OR 5.35, 95% CI 0.84–34.12, p=0.036) and for SAH, TBI, ICH, and brain tumor, the interaction terms all approached statistical significance (p=0.036-0.051), suggesting that more positive fluid balance might be associated with an increased risk of death. In contrast, infarct showed no such pattern (p = 0.256). Fluid type could not be distinguished in this dataset, but prior studies suggest composition may further modify outcomes. Conclusion: Early fluid balance shows diagnosis-specific prognostic value in neurocritical care, with fluid overload strongly linked to mortality in SAH, TBI, ICH and Brain tumor. Future studies should integrate fluid type alongside balance to refine individualized strategies.